Examining the effects of negative emotions on review helpfulness: The moderating role of product price. (February 2023) - Xu, Chengcheng; Zheng, Xiabing; Yang, Feng
Abstract: Negative emotional contents have been demonstrated to be persuasive when consumers judge review helpfulness across many existing studies. Drawing on emotions as social information (EASI) theory, signaling theory, and cognitive appraisal theory, we extended the current understanding of this underlying mechanism by considering the moderating role of the product price, an underestimated environmental signal. We focused on two negative emotions prominent in review content: anger and anxiety. A data sample of 73, 408 reviews of businesses with three different price levels from Yelp.com was analyzed to explore how anger and anxiety embedded in online reviews impact consumers' perceptions of review helpfulness and how product price moderates the relationship between these two emotions and review helpfulness. The results of linear regression analyses show that anger and anxiety positively impact review helpfulness in most cases, and product price moderates their relationships. Furthermore, our findings suggest that the positive effects of both discrete emotions on review helpfulness decrease as the price increases, and this influence is more pronounced in an angry emotion. Our findings advance the knowledge of discrete emotions on review helpfulness and provide practical insights for online retailers and third-party platforms to manage posted reviews efficiently. Highlights: We study the effects of negative emotions on review helpfulness. We examine the moderating role of product price. Results show that anger and anxiety embedded in reviews positively affect review helpfulness. Results reveal that the product price has a moderating effect between these two emotions and review helpfulness. Results indicate that the moderating effect is more pronounced in the relationship between anger and review helpfulness.